HUBUNGAN FREKUENSI ANTENATAL CARE DENGAN PENGETAHUAN TENTANG RESIKO TINGGI KEHAMILAN - KUSUMAWATI, ENDAH; MULYANI, ROSINA (AKADEMI KESEHATAN RAJEKWESI BOJONEGORO, 2015)
ABSTRACT Based on the reality of more than 90 % of maternal deaths are caused by obstetric complications , which often can not be foreseen at the time of pregnancy or childbirth . The high maternal mortality rate in Indonesia , largely due to bleeding ( 28 % ) , eclampsia ( 24 % ) , infection ( 11 % ) , abortion ( 5 % ) , or obstructed ( 5 % ) . Only about 5 % of maternal deaths are caused by diseases that worsen as a result of pregnancy , such as heart disease and chronic infections . It is very worrying , it turns out of the total cases of postpartum hemorrhage , only 7 people who did the ANC regularly , the condition is likely due to lack of knowledge of mothers on high- risk pregnancy , because she did not regularly conduct checks kehamilan.tujuan this study was to determine Knowledge ANC frequency relationship with pregnant women about the High Risk Pregnancy in the District Jatiblimbing Dander. This research is analytical research with cross sectional approach.Results of analysis using SPSS 12.0 was obtained chi-square value of 18.633 with a probability of 0.000 , while the Chi square table at df = 3 at 7.81 . Conclusions The frequency of ANC had a significant relationship with the knowledge of high-risk pregnancy in Puskesmas Kalitidu Bojonegoro . Keywords : Antenatal Care , Knowledge of Risk Pregnancy